Delay Notification of PT Kusumasentral Kencana Share Acquisition By PT Inter Sarana Prabawa (Study of KPPU Verdict Number 10/KPPU-M/2021) - Prescelly, Cindy; Setyawan, Fendi; Adiwibowo, Yusuf (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Laws were created as guidelines for social life and aim to harmonize and maintain order in social life. Law also has a role in economic development in Indonesia. Therefore, law is needed as a way out to avoid conflicts that often occur amidst the limited rights possessed by humans themselves, especially legal certainty regarding the development of a business, especially in the world of business competition. Case with Decision Number 10/KPPU-M/2021 where the case in this Decision is that there was a delay in notification of the takeover of PT shares. Kusumasentral Kencana by PT Inter Sarana Prabawa. The reported party, namely PT Inter Sarana Prabawa, violated Law Number 5 of 1999 concerning Prohibition of Monopolistic Practices and Unfair Business Competition and Government Regulation Number 57 of 2010 concerning Mergers or Consolidations of Business Entities and Takeovers of Company Shares which could Result in Monopoly Practices and Competition. Unhealthy Business. Analyze and answer legal issues related to the problem in this thesis, namely what is the ratio decidendi from Decision Number 10/KPPU-M/2021 regarding the delay in notification of the takeover of PT shares. Kusumasentral Kencana by PT Inter Sarana Prabawa? What are the legal consequences for business actors who violate the provisions of Article 29 of Law Number 5 of 1999. The aim of this research is, among other things, to determine the ratio decidendi from Decision Number 10/KPPU-M/2021 regarding the delay in notification of the takeover of PT shares. Kusumasentral Kencana by PT Inter Sarana Prabawa and find out the consequences for business players who violate the provisions of Article 29 of Law Number 5 of 1999. This research applies a normative juridical research type and uses a conceptual approach and a statutory approach. Then, the legal materials used are primary legal materials, secondary legal materials and non-legal materials The conclusion of this thesis contains conclusions and suggestions, where the conclusion contains Decision Number 10/KPPU-M/2021 which has been decided by the Commission Council in accordance with the provisions of Business Competition Law in Indonesia in this case the Commission Council decided that the Reported Party is PT Inter Sarana Prabawa declared to legally and convincingly violate the provisions of Article 29 of Law Number 5 of 1999 concerning Prohibition of Monopoly Practices and Unfair Business Competition. Then, the second conclusion is the legal consequences of unfair business competition resulting from the Delay in Notification of the Takeover of PT Shares. Kusumasentral Kencana by PT Inter Sarana Prabawa which violates the provisions of Article 29 of Law Number 5 of 1999, then OPT Inter Sarana Prabawa as the Reported Party is subject to sanctions in the form of an administrative fine of Rp. 1000,000,000.00 (one billion rupiah).